Question
upstudy study bank question image url

s) For the linear transformation \( L: \mathbb{R}^{2} \rightarrow \mathbb{R}^{3} \) given by \[ L((x, y))=(x+2 y,-x, 0) \] find the matrix \( A_{B C} \) for \( L \) with respect to the bases \[ B=\{(1,3),(-2,4)\}, C=\{(1,1,1),(2,2,0),(3,0,0)\} \]

Ask by Kelley Bob. in Russia
Dec 16,2024

Upstudy AI Solution

Tutor-Verified Answer

Answer

The matrix \( A_{B C} \) for the linear transformation \( L \) is: \[ A_{B C} = \begin{pmatrix} 0 & 0 \\ -\frac{1}{2} & 1 \\ \frac{8}{3} & \frac{4}{3} \end{pmatrix} \]

Solution

To find the matrix \( A_{B C} \) for the linear transformation \( L: \mathbb{R}^{2} \rightarrow \mathbb{R}^{3} \) with respect to the bases \( B \) and \( C \), we will follow these steps: 1. **Apply the transformation \( L \) to the basis vectors in \( B \)**. 2. **Express the results in terms of the basis \( C \)**. 3. **Form the matrix \( A_{B C} \) using the coefficients from the previous step**. ### Step 1: Apply \( L \) to the basis vectors in \( B \) The basis \( B \) consists of the vectors \( (1, 3) \) and \( (-2, 4) \). 1. For the first basis vector \( (1, 3) \): \[ L((1, 3)) = (1 + 2 \cdot 3, -1, 0) = (1 + 6, -1, 0) = (7, -1, 0) \] 2. For the second basis vector \( (-2, 4) \): \[ L((-2, 4)) = (-2 + 2 \cdot 4, -(-2), 0) = (-2 + 8, 2, 0) = (6, 2, 0) \] ### Step 2: Express the results in terms of the basis \( C \) The basis \( C \) consists of the vectors \( (1, 1, 1) \), \( (2, 2, 0) \), and \( (3, 0, 0) \). We need to express \( (7, -1, 0) \) and \( (6, 2, 0) \) as linear combinations of the vectors in \( C \). #### Expressing \( (7, -1, 0) \) We want to find coefficients \( a, b, c \) such that: \[ a(1, 1, 1) + b(2, 2, 0) + c(3, 0, 0) = (7, -1, 0) \] This gives us the system of equations: 1. \( a + 2b + 3c = 7 \) 2. \( a + 2b = -1 \) 3. \( a = 0 \) From the third equation, we have \( a = 0 \). Substituting \( a = 0 \) into the second equation: \[ 0 + 2b = -1 \implies b = -\frac{1}{2} \] Now substituting \( a = 0 \) and \( b = -\frac{1}{2} \) into the first equation: \[ 0 + 2(-\frac{1}{2}) + 3c = 7 \implies -1 + 3c = 7 \implies 3c = 8 \implies c = \frac{8}{3} \] Thus, we have: \[ (7, -1, 0) = 0(1, 1, 1) - \frac{1}{2}(2, 2, 0) + \frac{8}{3}(3, 0, 0) \] This corresponds to the coefficients \( (0, -\frac{1}{2}, \frac{8}{3}) \). #### Expressing \( (6, 2, 0) \) We want to find coefficients \( d, e, f \) such that: \[ d(1, 1, 1) + e(2, 2, 0) + f(3, 0, 0) = (6, 2, 0) \] This gives us the system of equations: 1. \( d + 2e + 3f = 6 \) 2. \( d + 2e = 2 \) 3. \( d = 0 \) From the third equation, we have \( d = 0 \). Substituting \( d = 0 \) into the second equation: \[ 0 + 2e = 2 \implies e = 1 \] Now substituting \( d = 0 \) and \( e = 1 \) into the first equation: \[ 0 + 2(1) + 3f = 6 \implies 2 + 3f = 6 \implies 3f = 4 \implies f = \frac{4}{3} \] Thus, we have: \[ (6, 2, 0) = 0(1, 1, 1) + 1(2, 2, 0) + \frac{4}{3}(3, 0, 0) \] This corresponds to the coefficients \( (0, 1, \frac{4}{3}) \). ### Step 3: Form the matrix \( A_{B C} \) The matrix \( A_{B C} \) is formed by taking the coefficients we found for each transformed basis vector and placing them in columns: \[ A_{B C} = \begin{pmatrix} 0 & 0 \\ -\frac{1}{2} & 1 \\ \frac{8}{3} & \frac{4}{3} \end{pmatrix} \] Thus, the final answer is: \[ A_{B C} = \begin{pmatrix} 0 & 0 \\ -\frac{1}{2} & 1 \\ \frac{8}{3} & \frac{4}{3} \end{pmatrix} \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To find the matrix \( A_{B C} \) for the linear transformation \( L: \mathbb{R}^{2} \rightarrow \mathbb{R}^{3} \) with respect to the bases \( B \) and \( C \), we follow these steps: 1. **Apply the Transformation to the Basis Vectors**: First, we need to apply \( L \) to each vector in the basis \( B \). - For \( (1, 3) \): \[ L((1, 3)) = (1 + 2 \times 3, -1, 0) = (1 + 6, -1, 0) = (7, -1, 0) \] - For \( (-2, 4) \): \[ L((-2, 4)) = (-2 + 2 \times 4, 2, 0) = (-2 + 8, 2, 0) = (6, 2, 0) \] Now we have: \[ L((1, 3)) = (7, -1, 0) \quad \text{and} \quad L((-2, 4)) = (6, 2, 0) \] 2. **Express Results in Terms of Basis \( C \)**: Next, we must express each of the results in terms of the basis \( C = \{(1, 1, 1), (2, 2, 0), (3, 0, 0)\}\). To find the coordinates of \( (7, -1, 0) \) in terms of the basis \( C \): \[ (7, -1, 0) = a(1, 1, 1) + b(2, 2, 0) + c(3, 0, 0) \] This leads to the system of equations: - \( a + 2b + 3c = 7 \) - \( a + 2b = -1 \) - \( a = 0 \) Solving this, we find \( a = 0 \), thus substituting: \[ 0 + 2b + 3c = 7 \quad \Rightarrow \quad 2b + 3c = 7 \] From \( 0 + 2b = -1 \) we have \( b = -\frac{1}{2} \). Substituting this into the first equation gives: \[ 2(-\frac{1}{2}) + 3c = 7 \quad \Rightarrow \quad -1 + 3c = 7 \quad \Rightarrow \quad 3c = 8 \quad \Rightarrow \quad c = \frac{8}{3} \] Therefore, \((7, -1, 0) = 0(1,1,1) - \frac{1}{2}(2,2,0) + \frac{8}{3}(3,0,0)\), whose coordinate vector in basis \( C \) is \( \begin{pmatrix} 0 \\ -\frac{1}{2} \\ \frac{8}{3} \end{pmatrix} \). Now, for \( (6, 2, 0) \): \[ (6, 2, 0) = a(1, 1, 1) + b(2, 2, 0) + c(3, 0, 0) \] We set up the equations: - \( a + 2b + 3c = 6 \) - \( a + 2b = 2 \) - \( a = 0 \) Again \( a = 0 \) leads to: \[ 0 + 2b + 3c = 6 \quad \Rightarrow \quad 2b + 3c = 6 \] From \( 0 + 2b = 2 \) we find \( b = 1 \). Then substituting into the first equation gives: \[ 2(1) + 3c = 6 \quad \Rightarrow \quad 2 + 3c = 6 \quad \Rightarrow \quad 3c = 4 \quad \Rightarrow \quad c = \frac{4}{3} \] Thus, \((6, 2, 0) = 0(

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy